A Comparison of Triamcinolone Acetonide Econazole Cream and Nystatin Suspension in Treatment of Otomycosis. (3rd November 2020) - Chen, Qingguo; Chu, Hanqi; Tao, Yanling; Peng, Liyan; Zhou, Liangqiang; Liu, Lei; Wu, Xiaohui
Abstract : Objectives/Hypothesis: To compare the efficacy and adverse effects of triamcinolone acetonide econazole cream and nystatin suspension in the treatment of otomycosis, and to determine the clinical features, predisposing factors, and etiology of otomycosis. Study Design: A prospective study. Methods: A prospective clinical trial was conducted on 786 patients diagnosed with otomycosis. The study population was randomly divided into two treatment groups of triamcinolone acetonide econazole cream (TAEC) and nystatin suspension in a 1:1 ratio. After clearing all fungal deposits in the external auditory canal, the antimycotic drugs were locally applied for at least 2 weeks. The efficacy and adverse effects were compared between the two antifungal reagents by statistical analysis. Meanwhile, patient clinical data were collected to find out the clinical features, predisposing factors, and etiology. Results: Pruritis was the most common symptom and Aspergillus niger was the leading fungal pathogen. There was high association (44.5%) of otomycosis with a history of unclean ear picking. The cure rate was 97.6% in the TAEC group and 73.5% in the nystatin group ( P < .01). Treatment with TAEC resulted in 2.4% of patients complaining of discomforts (irritant dermatitis, otalgia, or headache) versus 59.8% of patients complaining discomforts treated with nystatin ( P < .01). The residue rate of antifungals was 1.9% in the TAEC group and 89.9% in the nystatin group ( P < .01) at the end of treatment. Conclusions: Thoroughly cleaning of the external auditory canal followed by local use of TAEC under endotoscope is an effective, convenient, and well‐tolerated treatment for otomycosis. Level of Evidence: 1 Laryngoscope, 131:E1640–E1646, 2021